EFFECT OF RATIO VARIATION Mg / AL IN SYNTHESIS OF HYDROTALSIT WITH HYDROTHERMAL COPRECIPITATION METHOD - Sri Handayani; Cahyorini Kusumawardani; Kun Sri Budiasih (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2014)
Catalyst are divided into two kinds, homogeneous and heterogeneous catalysts. The catalys tthat constantly developed isa heterogeneous catalyst because could be separated easily and reuseable. The purpose of this research were synthesis and characterization of hydrotalcite Mg/Al as a heterogeneous catalyst which can be use din the aldol condensation reaction. Synthesis hydrotalcite was conducted by hydrothermal coprecipitation method. Synthesis performed with variations mol Mg/Alat a temperature hydrothermal 1000C for 15 hours. Hydrotalcite as a heterogeneouscatalyst preparation was done by calcinationat 4000C. Characterization of synthesized hydrotalcyte was performed by FTIR to identified functional group and XRD analysis to characteriz edits structure. The results showed that the optimum conditions for the synthesized hydrotalcite was obtained atmole ratio Mg/Al3:1.